ChemInform Abstract: Rapid Microwave Synthesis and Structural Phase Diagram of LnxY1‐xMnO3. Issue 40 (30th September 2014) - Marlton, Fred P.; Goossens, Darren J.; White, Reyner; Hutchison, Wayne D.
Abstract Polycrystalline 1 g samples of Y1‐xLnxMnO3 (Ln: La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, In; x = 0—0.5) are prepared by solid state reaction of stoichiometric amounts of Y2O3, MnO2, and Ln2O3 or Pr6O11 (microwaves, 800—1400 °C, 30—100 min).